KINERJA USAHATANI PADI DENGAN MESIN TRANSPLANTER DALAM RANGKA EFISIENSI TENAGA KERJA - Dewi Sahara; Ekaningtyas Kushartanti; Tota Suhendrata (Universitas Sebelas Maret, 2013)
Rice is still the main food staple for Indonesian people, therefore rice commodity has a strategic position either on economics, environmental, social and political aspect. Lately, some rice production centre area in Central Java have experienced a scarcity in labour specially for rice seedling activity. To solve this problem labour efficiency is needed by using transplanter to cultivate rice seed. The objective of this study are to know the efficiency of labor time and to identify the perfomance of rice farming system with transplanter. This study was done in Klaten District by using survey method to 30 rice farmers. To identify efficiency of labor time with compare of time spent on farm between manually and using transplanter, whereas to identify the perfomance of rice farming system with transplanter BCR (Benefit Cost Ratio) can be used. The result showed that the labour needed for seedling until cultivating manually is 32,79 of male’s hours and 23,79 of female’s hours, whereas by using it is transplanter only needed 18,67 male’s hours and none for female’s hours. If BCR with and no transplanter compared, rice farming after using transplanter has a higher (3,56) feasibility compare to none it (2,35). Therefore, to increase production and farmer’s income, as well as labour efficiency also were it is recommended to use transplanter.